Postnatal mothers and government health programs: a rural-urban cross-section study in India - Rutuja Karpe; Mitra, Suroshree (International Journal Of Community Medicine And Public Health, 2025)
Background: Government schemes for maternal and child health aim to improve the well-being of postnatal mothers and their children through financial, nutritional, and healthcare support. However, awareness and utilization remain inadequate, especially in rural areas, due to factors such as low literacy, poor communication, and accessibility issues. This study was conducted to assess and compare the awareness and utilization of these schemes among postnatal mothers in rural and urban areas of India. Methods: This descriptive cross-sectional study was conducted from May 2025 to September 2025 in Pune city among postnatal mothers aged 18 to 35 years. A total of 146 mothers were selected using a non-probability convenient sampling technique. A participant information sheet was provided, and written informed consent was obtained from all participants. Data were collected using a self-administered questionnaire. Results: Among 146 postnatal women with a mean age of 24.6 years for rural areas and 25.1 years for urban areas. Results showed that there were significantly less awareness and utilization of government schemes in rural areas than urban areas. Conclusions: Awareness and utilization remain poor in rural areas and suboptimal in urban areas. Mission Indradhanush stands out, showing good utilization even with low awareness due to effective programme delivery.